Tantalum Nanoparticles Reinforced PCL Scaffolds Using Direct 3D Printing for Bone Tissue Engineering - Xiong, Zixuan; Liu, Wenbin; Qian, Hu; Lei, Ting; He, Xi; Hu, Yihe; Lei, Pengfei (Frontiers in Materials, 2021)
Polycarbonate(PCL) has been widely used in tissue engineering, but its hydrophobicity and low biological activity limit its further promotion and application. By adding nanoparticles, the hydrophilicity and biological activity of PCL can be improved. In this study, different amounts of Ta (1%wt-10%wt) were added to PCL, and then their mechanical and biological properties were studied in vitro. XRD found that 5%Ta-PCL has the highest crystallinity. At the same time, cell experiments CCK8, cell adhesion, osteogenic differentiation, and osteogenesis related gene expression showed that Ta can enhance the mechanical and biological properties of PCL, while 5% Ta-PCL showed the best mechanical and biological properties. This composite of tantalum and PCL could have a clinical potential for orthopedic implants.